Implementation Of Teak Furniture Sales Information System In Mass Furniture Shop - Zulfitri Yani; Nurmaliana Pohan; Juna Eska (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
The rapid development and growth of information technology has a positive impact on agencies engaged in industry, sales, and services. Currently, sales are no longer carried out by sellers and buyers who meet face-to-face at the point of sale. Sales can already be done without having to go to the point of sale, and the seller and the buyer do not have to meet in person. Sales systems such as utilizing internet services for buying and selling online This research was conducted at the Mass Furniture Store using a field research methodology and library research. The Mass Furniture Shop is a shop that sells teak furniture. In selling furniture, it turns out that the shop has problems providing information to the public about the activities that exist in the store. Data processing is still done manually, or, in other words, there is no special program designed to process sales data, so the preparation of sales reports often experiences delays. The Mass Furniture Store's website design for socialization media, ordering media, and online sales media is built with the PHP programming language and MySQL database, and it is expected to optimize product sales, facilitate sales transactions, and make data processing faster, more precise, and more efficient. With the design of the website as a medium for socializing, selling, and ordering goods online, it can provide convenience for users, both the general public and customers, to get to know the Mass Furniture Store more easily, closely, and without being limited by space or time.